microRNA-210 and microRNA-3570 Negatively Regulate NF-κB-Mediated Inflammatory Responses by Targeting RIPK2 in Teleost Fish - Su, Hui; Chang, Renjie; Zheng, Weiwei; Sun, Yuena; Xu, Tianjun (Frontiers in Immunology, 2021)
Pathogen infection can cause the production of inflammatory cytokines, which are key mediators that cause the host's innate immune response. Therefore, proper regulation of immune genes associated with inflammation is essential for immune response. Among them, microRNAs (miRNAs) as gene regulator have been widely reported to be involved in the innate immune response of mammals. However, the regulatory network in which miRNAs are involved in the development of inflammation is largely unknown in lower vertebrates. Here, we identified two miRNAs from miiuy croaker (Miichthys miiuy), miR-210 and miR-3570, which play a negative regulatory role in host antibacterial immunity. We found that the expressions of miR-210 and miR-3570 were significantly upregulated under the stimulation of Gram-negative bacterium vibrio harveyi and LPS (lipopolysaccharide). Induced miR-210 and miR-3570 inhibit inflammatory cytokine production by targeting RIPK2, thereby avoiding excessive inflammation. In particular, we found that miR-210 and miR-3570 negatively regulate antimicrobial immunity by regulating the RIPK2-mediated NF-κB signaling pathway. The collective results indicated that both miRNAs are used as negative feedback regulators to regulate RIPK2-mediated NF-κB signaling pathway and thus play a regulatory role in bacteria-induced inflammatory response.